Improving channel maintenance methods for Egypt's irrigation systems - Schantz, Frederick F., author; Dixon, Robert E., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
After the construction of the High Aswan Dam in Egypt (1950s), the channel maintenance methods adopted by Egypt's Department of Irrigation included the employment of heavy, inefficient construction equipment that was utilized without an effective maintenance program. By the 1980s, these practices had seriously damaged Egypt's irrigation and drainage channel prisms and embankments, and were failing to effectively control the growing population of aquatic weeds. In an effort to improve this condition, the Channel Maintenance Project was formulated (1986) by the Egyptian Ministry of Public Works and Water Resources, with support from the International Bank for Reconstruction and Development and the United States Agency for International Development. The project's primary objective was to improve ad hoc channel maintenance practices by replacing the established system of channel embankment excavation with an efficient preventive maintenance program that included a balanced cycle of weed control mowing, herbicide treatment and desilting. A variety of modern channel maintenance equipment were used, including hydraulic excavator-mounted shallow-draft buckets and weed mowers, and motorized herbicide sprayers. Project efforts began in June 1989 and are planned throughout the 1990s.
Irrigation and water resources in the 1990's
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.